2015
DOI: 10.1002/alr.21622
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐institutional study of risk factors for perioperative morbidity following transnasal endoscopic pituitary adenoma surgery

Abstract: Postoperative endoscopic pituitary adenoma surgery complications are associated with tumors with intraventricular extension, preoperative radiation, as well as common patient comorbidities. Identification of these factors may permit implementation of strategies to reduce postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 26 publications
6
76
2
Order By: Relevance
“…retrospectively evaluated over 1000 patients with sellar lesions (craniopharyngioma and pituitary adenomas) from 7 different institutions and demonstrated a significantly higher postoperative CSF leak in patients with high BMI. A similar review of nearly 1000 patients with sellar lesions by Boling et al . similarly showed a significant increase in CSF leak rates with BMI >30.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…retrospectively evaluated over 1000 patients with sellar lesions (craniopharyngioma and pituitary adenomas) from 7 different institutions and demonstrated a significantly higher postoperative CSF leak in patients with high BMI. A similar review of nearly 1000 patients with sellar lesions by Boling et al . similarly showed a significant increase in CSF leak rates with BMI >30.…”
Section: Complicationsmentioning
confidence: 99%
“…However, Karnezis et al . and Boling et al . demonstrated that a younger age was significantly associated with reconstructive failure, though their data set may have overlapped.…”
Section: Complicationsmentioning
confidence: 99%
“…In a multi-institutional study of risk factors for perioperative morbidity following endoscopic pituitary surgery reported by Boling et al 45) , adverse events including intracranial/systemic complications, reoperation, readmission, and death occurred in 23.8% of 982 patients. Most commonly, these events were readmission in 15.4% of cases and reoperation in 6.5% of cases.…”
Section: Complicationsmentioning
confidence: 99%
“…CD must be distinguished from ectopic sources of ACTH; non-invasive tests have relatively low sensitivity and specificity 1 2. Because surgery carries significant morbidity,3 performing a minimally invasive procedure that is safe to demonstrate central-peripheral gradient and justify a risky surgical procedure is often an appropriate diagnostic step before resection.…”
Section: Introductionmentioning
confidence: 99%